(untitled) (Studia austriaca, 2023)
The Austrian novelist, essayist and journalist Maria Lazar (1895-1948), only recently rediscovered, who was a contemporary of Thomas Mann and an acquaintance of Bertolt Brecht, wrote many different types of texts. Considered a promising talent back in Vienna, the reception of her works decreased during Lazar’s years in exile. The following contribution aims to reconstruct the dynamics of her marginalization and takes a closer look at the socially critical dimension of No Right to Live and Die Eingeborenen von Maria Blut [The Natives of Maria Blood].